Application background and mechanism of short-chain fatty acids in sepsis-associated encephalopathy - Zhang, Qiulei; Lu, Chang; Fan, Weixuan; Zhang, Jingxiao; Yin, Yongjie (Frontiers in Cellular and Infection Microbiology, 2023)
Sepsis-associated encephalopathy (SAE) is a frequent brain dysfunction in patients with sepsis, which is manifested as delirium, cognitive impairment, and abnormal behaviors. The gut microbiome and short-chain fatty acids (SCFAs) are particularly associated with neuroinflammation in patients with SAE, and they have noticeably attracted scholars’ attention. The association of brain function with the gut-microbiota-brain axis was frequently reported. Although the occurrence, development, and therapeutic strategies of SAE have been extensively studied, SAE remains a critical factor in determining the long-term prognosis of sepsis and is typically associated with the high mortality. This review concentrated on the interaction of SCFAs with microglia in the central nervous system, and discussed the anti-inflammatory and immunomodulatory effects of SCFAs by binding to free fatty acid receptors or acting as histone deacetylase inhibitors. Finally, the prospects of dietary intervention using SCFAs as dietary nutrients in improving the prognosis of SAE were reviewed.